Study of Two Different Volumes of 0.75% Ropivacaine for Ultrasound Guided Supraclavicular Brachial Plexus Block on Successful Blockade and Diaphragmatic Motility - Prasad, J. N.; Adhikari, S.; Singh, S. N.; Subedi, A.; Thapa, P.; Guddy, K. M.; Sarraf, D. P. (Kathmandu University Medical Journal, 2022)
Background Use of ultrasound guidance during supraclavicular brachial plexus block allows the usage of a lower anesthetics dose and minimizing unwanted effects of the anesthesia. Objective To compare the success of sensory blockade and the incidence of hemidiaphragmatic dysfunction in patients receiving two different volume of 0.75% Ropivacaine for ultrasound guided supraclavicular brachial plexus block. Method A prospective randomized double-blinded comparative study was conducted. Group A patients (n=30) received 20 ml and Group B (n=30) received 25 ml of 0.75% Ropivacaine for ultrasound guided supraclavicular brachial plexus block. Hemodynamic parameters, oxygen saturation, diaphragmatic excursion, onset of sensory blockade and time for completion of blockade were measured. Independent t-test, Chi-square test and Mann-Whitney U test were used to analyze the data at p value of less than 0.05 using Statistical Package for Social sciences (version 11.5). Result At 30 minutes, 29 (96.67%) patients in group B and 27 (90.0%) patients in group A had no sensation in median, radial, ulnar, musculocutaneous and medial cutaneous nerves territories; however, it was not significant statistically (p value > 0.05). At 30 minutes in Group A, 25 (83.33%) patients had no diaphragmatic hemiparesis and five (16.67%) patients had partial diaphragmatic hemiparesis. However, three (10%) patients had no diaphragmatic hemiparesis in Group B, 25 (83.33%) patients had partial and two (6.67%) patients had complete diaphragmatic hemiparesis and it was statistically significant (p < 0.05). Age and sex had no effect on diaphragmatic hemiparesis in both groups (p value > 0.05). Conclusion The patients receiving lower volume of Ropivacaine had less incidence of hemidiaphragmatic dysfunction with similar sensory blockade as compared to the patients receiving higher volume of Ropivacaine.